Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol

Metal deficiency tailored by the 18-electron rule stabilizes metal-based inorganic compounds - Singh, Ashutosh Kumar; Mumbaraddi, Dundappa; Mishra, Vidyanshu; Roy, Soumyabrata; Vinod, C. P.; Peter, Sebastian C. (Chemistry of Materials, 2023)
The 18-electron (18-e(-)) rule is typicallyrestrictedto predicting the stability of transition-metal-based complexes. Herein,we report the use of the 18-e(-) to predict the stabilityin a family of intermetallics MNiSn (M = V, Cr, Fe, and Co) crystallizingin the Co1.75Ge structure type. Site deficiencies at theM site obtained from single-crystal X-ray diffraction are understoodas attaining a stable noble gas electronic configuration. The densityfunctional theory -based structure calculation confirms that the deficientstructure is more stable than the ideal occupation available at thecrystal lattice. MnNiSn, which crystallizes in the half-Heusler crystalstructure, depicts the role of covalent radii of the constituent elementsin determining the crystal structure. Using X-ray absorption spectroscopyand X-ray photoelectron spectroscopy, the local structure of the above-mentionedcompounds was also elucidated, supporting the role of deficiency tunedvalence fluctuation to attain a 18-e(-) configurationthat eventually leads to the formation of stable compounds.

Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis